Electric fields calculation of lightning return-strokes in the presence of an attachment point above the ground. (1st October 2022) - Li, Quanxin; Gong, Zixuan; Wang, Jianguo; Cai, Li; Zhou, Mi; Fan, Yadong
Abstract: The radiated electromagnetic fields and derivative waveforms from lightning discharge were directly related with its inner physical process. The return stroke initiated from ground (RSG) and the return stroke initiated from an attachment point (RSAP) were analyzed. Two types of current waveform from Gamerota et al. (2012) and Rachidi et al. (2001), including both the first and subsequent return strokes, were simulated in the presented paper. Both waveforms of the electric field and electric field derivative were analyzed. The electric fields were characterized by an obvious superimposed initial peak on the rising edge, the electric field derivative was featured by a bipolar waveshape with noticeably negative overshoot in the second cycle. The downward return stroke current component is the main reason for the superimposed initial peak in the electric field and the bipolar waveshape with noticeably negative overshoot in the electric field derivative. The subsequent return stroke with larger max steepness from Gamerota et al. (2012) shows more noticeable superimposed initial peak than that of Rachidi et al. (2001). The subsequent return stroke shows more noticeable differences than that of the first return stroke. The peak value enhancements at 100 km are similar to that at 15 km. The changes were less than 0.5% for first return strokes, and 1.5% for subsequent return strokes. Parameter sensitivity on the electric fields and derivative waveforms were also presented. Highlights: The return stroke initiated from ground (RSG) and the return stroke initiated from an attachment point (RSAP) were analyzed. Both waveforms of the electric field and electric field derivative were analyzed. Parameter sensitivity on the electric fields and derivative waveforms were also presented.